The kidney in heart failure - Bakris, George L. (Springer US, 2012)
Chronic Kidney Disease (CKD) is a recognized risk factor for cardiovascular events and death.  The coexistence of CKD and heart failure is increasing in prevalence worldwide and requires a unique and subtle approach to patient management.   The Kidney in Heart Failure focuses on the changes that occur in kidney physiology as a function of a failing heart.  This comprehensive resource covers epidemiology, pathophysiology, management of kidney disorders and advances in nephropathy management.  In addition, the latest therapies, common heart failure dilemmas and kidney disease markers are included.  Each chapter is co-authored by a Nephrologist and Cardiologist, offering a unified perspective to these chronic conditions.   This indispensible volume provides the reader with the depth-of-knowledge needed for assessing and treating the cardio renal patient.